2013
DOI: 10.1038/ejhg.2013.257
|View full text |Cite
|
Sign up to set email alerts
|

What hinders minority ethnic access to cancer genetics services and what may help?

Abstract: Ethnic disparities in use of cancer genetics services raise concerns about equitable opportunity to benefit from familial cancer risk assessment, improved survival and quality of life. This paper considers available research to explore what may hinder or facilitate minority ethnic access to cancer genetics services. We sought to inform service development for people of South Asian, African or Irish origin at risk of familial breast, ovarian, colorectal and prostate cancers in the UK. Relevant studies from the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
60
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(67 citation statements)
references
References 53 publications
7
60
0
Order By: Relevance
“…Equally important, we found higher uptake when patients had a discussion with a research staff member or their physician, suggesting that re‐contacting people in writing may not be the most effective strategy for offering updated MGPT. Additionally, we found that non‐White patients were more likely to not respond to the invitation for MGPT, raising the possibility for disparities in uptake of testing, consistent with previously published studies . Additionally, a study that surveyed patients retrospectively after MGPT did find higher distress and lower satisfaction among non‐White patients, providing strong rationale for additional studies to determine if outcomes differ for minority populations …”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Equally important, we found higher uptake when patients had a discussion with a research staff member or their physician, suggesting that re‐contacting people in writing may not be the most effective strategy for offering updated MGPT. Additionally, we found that non‐White patients were more likely to not respond to the invitation for MGPT, raising the possibility for disparities in uptake of testing, consistent with previously published studies . Additionally, a study that surveyed patients retrospectively after MGPT did find higher distress and lower satisfaction among non‐White patients, providing strong rationale for additional studies to determine if outcomes differ for minority populations …”
Section: Discussionsupporting
confidence: 87%
“…3 We did find that intent to perform mammog- found that non-White patients were more likely to not respond to the invitation for MGPT, raising the possibility for disparities in uptake of testing, consistent with previously published studies. 41,42 Additionally, a study that surveyed patients retrospectively after MGPT did find higher distress and lower satisfaction among non-White patients, providing strong rationale for additional studies to determine if outcomes differ for minority populations. 39 We acknowledge several limitations of this study.…”
Section: Discussionmentioning
confidence: 99%
“…9 In minority communities, low awareness of familial cancer risk and social and cultural beliefs, such as those that lead to stigma about hereditary cancer, also appear to contribute to disparities in the use of genetic services. 10 …”
Section: Using Genetics To Combat Diseasementioning
confidence: 99%
“…Data obtained from cancer referrals to Leicester's genetics service suggested that the number of Mendelian mutation carriers being seen in the clinic were less than would be expected given the catchment population size of 1 million; moreover, concerns were raised that referrals from Black and Minority Ethnic (BME) groups were also lower than would be expected given the large South-Asian community resident in the Leicester area [3] and that opportunities for earlier interventions in families were being missed through late referrals.…”
Section: Introductionmentioning
confidence: 96%